2020
DOI: 10.1175/jamc-d-19-0080.1
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Effect of Clouds at Ny-Ålesund, Svalbard, as Inferred from Ground-Based Remote Sensing Observations

Abstract: For the first time, the cloud radiative effect (CRE) has been characterized for the Arctic site Ny-Ålesund, Svalbard, Norway, including more than 2 years of data (June 2016-September 2018). The cloud radiative effect, that is, the difference between the all-sky and equivalent clear-sky net radiative fluxes, has been derived based on a combination of ground-based remote sensing observations of cloud properties and the application of broadband radiative transfer simulations. The simulated fluxes have been evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
63
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 53 publications
(76 reference statements)
12
63
0
Order By: Relevance
“…The surface cloud radiative effect (denoted as CRE throughout the study), which will be analyzed for the different humidity conditions, was derived from the broadband radiative transfer calculations by Ebell et al (2019) with the rapid radiative transfer model RRTMG for the analyzed period at Ny-Ålesund. The model provides vertically resolved shortwave (SW) and longwave (LW) up-and downward fluxes and heating rates.…”
Section: Surface Cloud Radiative Effectmentioning
confidence: 99%
See 3 more Smart Citations
“…The surface cloud radiative effect (denoted as CRE throughout the study), which will be analyzed for the different humidity conditions, was derived from the broadband radiative transfer calculations by Ebell et al (2019) with the rapid radiative transfer model RRTMG for the analyzed period at Ny-Ålesund. The model provides vertically resolved shortwave (SW) and longwave (LW) up-and downward fluxes and heating rates.…”
Section: Surface Cloud Radiative Effectmentioning
confidence: 99%
“…1 for the calculation of LW, SW, and net CRE, respectively. Ebell et al (2019) estimated the uncertainties in CRE using 10-min averaged fluxes observed by the baseline surface radiation network (BSRN). The uncertainties in CRE depend on averaging time.…”
Section: Surface Cloud Radiative Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of environmental conditions can effect cloud micro-and macro-physical properties. According to simulations over different surface types, changes in surface properties lead to changes in the thermodynamic structure of the atmospheric boundary layer, the extent of dynamical coupling of the cloud to the surface, and the microphysical properties of the MPC (Morrison et al, 2008;Li et al, 2017;Savre et al, 2015;Eirund et al, 2019). Also, observational evidence on the connection between changes in surface conditions and MPC occurrence (Morrison et al, 2018) as well as thermodynamic structure and droplet number concentration (Young et al, 2016) has been found.…”
Section: Introductionmentioning
confidence: 97%